Hodnotenie likvidity podniku - Bobáková, Viktória (Univerzita Pardubice, 1998)
The organization of the company clearance is a very important field of management, that is why it is important to give attention to it. These can be grouped into factors that influence the income (receipts, financial possession, short term lialibities, reserves) and into factors that influence the expenses (material, personal expenses, interest, investment expenses, short-term, lialibilities). On organization of the company clearance decide also indicators that we use for its planning, inspection and evaluation.
Keywords: podniky; finanční rozhodování; likvidita